Integration of the buyer–supplier interface for Global sourcing - Lydia Bals; Virpi Turkulainen (Operations Management Research, 2021)
While global sourcing often implies that the firm needs to, for example, redesign the procurement organization and make decisions on what to centralize and what to manage locally, global sourcing also has direct implications for management of the buyer–supplier interface. This study takes an organization design focus and addresses global sourcing organization design as well as provides illustrations on how to integrate the buyer–supplier interface for global sourcing. Integration is conceptualized as coordination and cooperation. The paper is based on an embedded unit case study of a global technical industrial product and service systems provider, TechInd (pseudonym). Data was collected from TechInd as well as from six of its suppliers. The findings indicate that the global sourcing organization structure, as well as the differences in the buyer's sourcing and supplier's sales organizations, pose requirements for management of the interface in terms of coordination and cooperation. Challenges arising particularly due to differences in geographical scope and level of centralization can be managed by introducing the key account role and alignment of incentives.
Keywords: 510; Global sourcing; Buyer–supplier relationship; Integration; Organizational design; Case study; Project-based operations